Youth groups sheep-fattening entrepreneurship as a springboard to enhancing sustainable farming and livelihoods in Ethiopia - Ekule, Muluken; Wamatu, Jane (All Africa Conference of Animal Agriculture, 2023)
The primary objective of this study was to promote collective entrepreneurship via the formation of sheep fattening groups and cooperatives by public and private engagement co-opted through coordination committees to improve vertical and lateral engagements in Ethiopia. The 1730 youth and women in 47 groups participated in sheep fattening activities in Amhara, Southern and Southwestern Ethiopian regions.